1989
DOI: 10.1002/ajmg.1320340408
|View full text |Cite
|
Sign up to set email alerts
|

Significance of cardiovascular malformations in cystic hygroma: A new interpretation of the pathogenesis

Abstract: Fetuses with cystic hygroma or loose skin of the neck were studied chromosomally and phenotypically to clarify the relation between neck abnormality and cardiovascular malformations. Of 12 fetuses, 9 had chromosome abnormalities: 4 with 45,X, 3 with trisomy 21, one each with trisomy 13, dup 6q. One had normal chromosomes. Two cases, in which chromosome analysis was unsuccessful, were morphologically suspected to be trisomy 13. Nine of the 12 fetuses had either bilateral cystic hygroma of the neck (7 cases) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 30 publications
(10 reference statements)
2
23
0
1
Order By: Relevance
“…This association was first noted in spontaneously aborted fetuses with TS that had large cystic hygromas (31). The nuchal cystic hygromas are collections of lymph associated with blind-ended jugular lymphatics (26,27,31,32). In fetuses that survive, the lymphatics develop and hygromas resolve during the latter half of gestation, leaving redundant skin folds of the neck.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This association was first noted in spontaneously aborted fetuses with TS that had large cystic hygromas (31). The nuchal cystic hygromas are collections of lymph associated with blind-ended jugular lymphatics (26,27,31,32). In fetuses that survive, the lymphatics develop and hygromas resolve during the latter half of gestation, leaving redundant skin folds of the neck.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of BAV determined in the present study pertains to TS individuals that have survived to age 7 years and older. The prevalence of aortic valve abnormalities and other congenital defects appears to be much higher in TS fetuses, with the great majority dying in utero due to circulatory failure (6,26,27). About 10% of newborns with TS have very serious cardiovascular defects, mainly hypoplastic left heart, and survival is poor (24).…”
Section: Discussionmentioning
confidence: 99%
“…They reported a 75% incidence of CHD that consisted almost exclusively of left-sided flow defects, including coarctation in 67%. Miyabara et al [1989] examined 12 aborted fetuses with nuchal cystic hygroma or loose nuchal skin and reported that of 4 fetuses with 45,X karyotype, all had coarctation along with other flowrelated HDs. Clark [ 19841 reviewed 193 cases of UllrichTurner syndrome and found an increased incidence of CHD in fetuses who had web neck (30%) vs. normal neck (9%).…”
Section: Discussionmentioning
confidence: 99%
“…Clark [26] suggested that the associated cardiovas cular malformations, primarily coarctation of the aorta and other defects in the spectrum of left heart obstruction, are the consequence of altered intracardiac blood flow due to compression of the ascending aorta by the distended intrathoracic lymphatic channels. Miyabara et al [18] noted that these fetuses have, in addition to the cystic hygromata and cardiac defects, generalised lymphatic and thymic hypoplasia. They hypothesised that the underlying mechanism for all these mal formations is decreased or delayed migration of neural crest cells and abnormal interaction with the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%